Delayed language development: grammatical features - Balčiūnienė, Ingrida; Kamandulytė-Merfeldienė, Laura (Baltistica, 2018)
The aim of the article is to discuss the features of delayed language development, focusing on the acquisition of the grammatical system on the basis of corpus data. The main object of the present investigation is longitudinal language data of three children (a late talker and a pair of twins). To describe the features of delayed language development, the language of the above-mentioned children has been compared to the language of typically developing children (two children). Thus, in total, the research material is comprised of five child language sub-corpora totaling 230,000 words. The present investigation has employed the methodology of long-term observation of natural language development, error analysis method, and statistical analysis methods. The results have shown that delayed specific language development (e.g. twins’ language) may be related to more difficulties in the acquisition of the grammatical system than delayed typical development. Thus, the research has demonstrated that delayed development influenced by the untypical situation is a key risk factor.